Pathways to Cybersex: Case-Report-Based Exploration. Issue 1 (January 2020) - Sharma, Manoj Kumar; Anand, Nitin; J., Ajith S.; Thakur, Pranjali Chakraborty; N., Suma; Sahu, Maya; John, Nisha; Tapatrikar, Ashwini; Biswas, Ankita; Vishwakarma, Akash; R., Archana; Singh, Priya; et al.
Abstract: The internet has become the preferred platform for use of webcam. The interactive online aspect of webcamming allows participants to have stimulating enjoyable experience for each act. There has been an increasing trend in users seeking help from the service for healthy use of technology (SHUT) specialty clinic for the management of pornography use. Clinical interviews were used to elicit details about their concern. The cases demonstrated the role of online behaviors especially cybersex in managing stress, free time, loneliness, boredom, as well as the need for novelty. It implies the need for screening the pathways to cybersex as well as to evolve intervention to manage these pathways in an Indian context.